Ghana - Kanye Ndu Bowi : An Indigenous Philosophical Context for Conflict Management - World Bank (Washington, DC, 2012)
This article intends to summarize findings from a study carried out by the author between the winter of 1995 and spring of 1996 among the Buems on the Ghana side of the Ghana-Togo border. The objective in this paper is to identify and discuss the main philosophical contexts within which the indigenous Buem conflict management system operates. The paper also assesses the relevance of these principles to the management of modern conflicts in the area, particularly land-related conflicts.